The role of prophylactic chest physiotherapy after cardiac valvular surgery: Is there one ? - S. B. de Charmoy; C. J. Eales (AOSIS, 2000)
A study was conducted to investigate whether there is a role for prophylactic chest physiotherapy in preventing pulmonary complications in-patients undergoing uncomplicated cardiac valvular surgery. 'Thirty patients were randomly divided into two groups. The patients in group I (n = 14) received instructions that they should cough after their operation and that they should get out of bed on the second post-operative day. The patients in group 2 (n = 16) were seen pre-operatively and treated post-operatively by a physiotherapist. The treatment consisted of breathing exercises, supported coughing and assistance with walking from the second post-operative day. These patients were seen twice daily on the first and second post-operative days and once daily on the third and fourth post-operative days. No patients in either group developed a pulmonary complication during their post-operative hospital stay. The incidence of hypoxaemia, chest X-ray abnormalities and length of post-operative stay were not significantly higher for the control group. The findings of this study suggest that the role of prophylactic chest physiotherapy following cardiac valvular surgery is questionable.